Role Optimization of Indigenous Institutions for Case of Violence Against Women and Children (Analysis Study in Aceh and Padang Provinces) - Husaini Husda; Zubaidah Zubaidah (Budapest International Research and Critics University, 2018)
Institutions as social control always succeed in regulating so that the social life of citizens can run in an orderly and smooth manner in accordance with prevailing traditions and norms. As has been functioning well in the past, both in Aceh and West Sumatra. Aceh with its gampong pageu, and West Sumatra with surau. Both reflect a blend of local wisdom (adat) and Islamic values in it. However, if you see the rampant cases of violence and sexual abuse that have occurred in women and children lately, it is not wrong to say that the role of institutions as social control began to weaken. Like the role of surau and gampong pageu which is slowly ignored and forgotten. Re-empowering social institutions means trying to restore the pattern of community behavior based on existing norms. For this reason, systematic efforts are needed in empowering social institutions by empowering social institutions in accordance with the changes and demands of the times.